1979
DOI: 10.1073/pnas.76.7.3504
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced damage to ocular lens cation pump: prevention by vitamin C.

Abstract: The cation pump activity of the ocular lens was damaged by exposure to light in the presence of riboflavin phosphate. The intensit of ight was similar to that used for reading purposes. The observed light-induced damage was due to superoxide or its derivatives, the superoxide being produced photochemically. Such damage was attenuated by vitamin C in amounts comparable to that in the aqueous humor. Thus, a new role for the high ascorbate level present in the anterior chamber fluid and the lens has been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(83 citation statements)
references
References 19 publications
(12 reference statements)
1
81
0
1
Order By: Relevance
“…NAD~and NADPH!NADP~redox couples linked to AR and sorbitol dehydrogenase, respectively (Carroll et al, 1986;Williamson et al, 1993;Thomas et al, 1994). AA is a well documented physiological antioxidant (Varma et a!., 1979;Organisciak et a!., 1985). Therefore, AA could have a dual effect, i.e., as an ARI-like agent and also as an antioxidant, and thus ameliorate the deleterious effects of long-term exposure to elevated glucose levels on MI metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…NAD~and NADPH!NADP~redox couples linked to AR and sorbitol dehydrogenase, respectively (Carroll et al, 1986;Williamson et al, 1993;Thomas et al, 1994). AA is a well documented physiological antioxidant (Varma et a!., 1979;Organisciak et a!., 1985). Therefore, AA could have a dual effect, i.e., as an ARI-like agent and also as an antioxidant, and thus ameliorate the deleterious effects of long-term exposure to elevated glucose levels on MI metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…PHAT lens and is present in very high concentrations in lens and aqueous humour [41]. Ascorbic acid has been demonstrated to be a potent scavenging agent of singlet oxygen [42] and superoxide [43]. Lowered ascorbic acid levels are commonly associated with cataract formation [6,25,41].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies have shown that high levels of the oxygen radicals superoxide and H202 are generated in the lens of photochemically-induced cataracts (Varma et al 1979;Spector et al 1993). Hz02 is also called a 'mobile time bomb' as it can react in a Fenton reaction to form the highly-damaging hydroxyl radical (Gutteridge & Halliwell,1 994).…”
Section: Photochemical Insult and Defencementioning
confidence: 99%